INTEGRATION OF RENEWABLE ENERGY AND IOT TECHNOLOGY FOR GEOTHERMAL TOURISM DEVELOPMENT IN PACITAN: INTEGRASI ENERGI TERBARUKAN DAN TEKNOLOGI IOT UNTUK PENGEMBANGAN WISATA GEOTHERMAL DI PACITAN - Retna Apsari; Herri Trilaksana; Pujiyanto; Yoga Uta Nugraha; Muhammad Syahril Mubarok; Prisma Megantoro; Sri Endah Nurhidayati (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Pacitan Regency, located between hills, mountains, and waters, boasts abundant natural resources, including geothermal potential and renewable energy. However, its remote location, far from the capital of East Java, has led to underutilization of these resources, particularly in the tourism sector. Objective: This initiative aims to develop eco-friendly tourist destinations integrated with IoT technology to enhance Pacitan's branding and recognition. Method: The project involves planning through Forum Group Discussions (FGD) and socialization, followed by technical implementation, publicity, recruitment of local cadres, and signing of integrity pacts. Subsequent steps include strengthening local identity, implementation, and program monitoring and evaluation. Results: The partnership has effectively addressed challenges related to infrastructure and planning for renewable energy and IoT-based geothermal tourism while adhering to sustainable development principles. Conclusion: The activity was successfully executed, receiving strong support from regional figures. The material delivery was precise, the target participant numbers were met, and there was significant collaboration with local communities and universities. The project has not only helped local partners but also contributed to Pacitan's potential for sustainable tourism development.